ACTUAL PROBLEMS OF COMPLIANCE WITH THE PRINCIPLES OFCRIMINALLAW - Nurtayev Рамазан Туякович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
Development of problems associated with the rethinking of certain fundamental elements of national criminal law, has a certain perspective, as well as increased scientific and practical significance in terms of the search for the best ways to make more clear adjustments to the state’s activity to strengthen the fight against criminal offenses in modern conditions. One of the fundamental provisions of the criminal law is a set of its principles, which is not fixed in the criminal law of our country. The lack of regulation of relations connected with the influence of the principles of criminal law, creates certain difficulties in the theory and practice of the organization of measures to combat criminal offenses in our country. All this suggests that it is necessary to make certain amendments to the current criminal legislation, aimed at the formulation of the principles of the criminal legislation of the Republic of Kazakhstan. The article deals with current issues of compliance with the principles of criminal law as one of the fundamental elements of the theory and practice of construction of criminal policy of our state. Development issues associated with the rethinking of certain fundamental elements of national criminal law, has a certain perspective, as well as increased scientific and practical significance in terms of the search for the best ways to make more clear the adjustment in activity of the state to strengthen the fight against criminal offenses in modern conditions. In turn, the modern realities of life bring to the agenda the need to take into account of the objective circumstances, that at present there have been significant changes in the quantitative and qualitative indicators of crime related to the greater part of the emergence of new types of crime, the intensification and expansion of organized criminality, here including transnational organized crime. These circumstances would be appropriate to consider as factors indicating that the science of criminal law and criminology development of guidelines, particularly aimed at the disclosure of the fundamental concepts, need to find new approaches and solutions. One of the fundamental provisions of the criminal law is a set of its principles, which is not fixed in the criminal law of our country. Within the framework of the principles of the doctrine of the right system it has been developing in a complex legal traditionally established dogma, to take its place in the structure of self-care a fundamental part of the theory and practice of law. In particular, the theory of law principles are developed on the basis of their elevation to the rank of guiding ideas, acting as a factor in penetrating the content of the right as well as its purpose, the essential basics and importance to society. The lack of regulation of relations connected with the influence of the principles of criminal law, creates certain difficulties in the theory and practice of the organization of measures to combat criminal offenses in our country. All this suggests that it is necessary to make certain amendments to the current criminal legislation, aimed at the formulation of the principles of the criminal legislation of the Republic of Kazakhstan.